Benzodithiophene based organic dyes for DSSC: Effect of alkyl chain substitution on dye efficiency. (October 2015) - Baldoli, Clara; Bertuolo, Stefania; Licandro, Emanuela; Viglianti, Lucia; Mussini, Patrizia; Marotta, Gabriele; Salvatori, Paolo; De Angelis, Filippo; Manca, Paola; Manfredi, Norberto; Abbotto, Alessandro
Abstract: A series of push–pull triarylamine organic dyes containing the benzo[1, 2- b :4, 5- b ′]dithiophene unit as a spacer and bearing alkyl chains in different positions of the molecule were synthesized. The new dyes1 –4 were characterized by optical and electrochemical measurements and density functional theory calculations and used as sensitizers in liquid dye-sensitized solar cells. The effect of alkyl chain position on dye properties and performances was investigated and dye1, bearing two 3, 7-dimethyloctyl groups on the benzodithiophene core, exhibited the best behaviour in term of light absorption and cell performance (PCE of 6.6%, to be compared with a PCE of 8.1% for N719-based device). The efficiency of the DSSC was highly dependent on the solvent used for the dye-sensitizing bath, which affects the position of the COOH/COO − equilibrium. Graphical abstract: Highlights: Synthesis and characterization of benzodithiophene-based dyes bearing alkyl chains. Effect of alkyl chain position on dye properties and performances was investigated. Dye with alkyl chains on benzodithiophene spacer showed the best performance. Solvent strongly affects the position of the COOH/COO − equilibrium of the dye. DSSC efficiency was highly dependent on the solvent used in the sensitizing bath.